ANALISA DAN PENANGANAN KERUSAKAN TERMOSTAT PADA AIR CONDITIONER SPLIT WALL - Ismail, KGS.M; Inten Suwono, Niedya; Prasetianto, Indra; Putra Pratama, Delvin; Ghufroon; Bimantoro, M.Dimas Aji (Jurnal Teknik Mekanikal Bandar Udara, 2023)
The world of Aviation Industry in Indonesia continues to experiencedevelopments in various fields. With this development, airports thatoperate must have adequate facilities. Airport buildings ranging fromterminals to supporting buildings must have a comfortable temperature.So here a tool is needed to regulate the room temperature of thebuildings at the airport. The tool in question is Air Conditioning (AC).This research is based on events that are often found in air conditioners.After analyzing, it was found that the thing that caused the airtemperature in the room to be unstable was damage to the thermostat component. Where the thermostat component functions as a sensor thatcontrols the temperature to be cooler / warmer as needed. With arelatively cool room temperature, this can make passengers feelcomfortable at the airport. Air Conditioning (AC) maintenance is veryimportant so that the condition of the AC components remains excellentand the engine can function properly without damage.